(untitled) (Movimenta (ISSN 1984-4298), 2021)
Purpose: To investigate velocity and cadence in people with multiple sclerosis (MS) submitted to different walking tasks, and to compare the results with those found in healthy control peers. Methods: One hundred thirty-three participants, sixty-six with MS and sixty-seven without MS, were enrolled in this study. Subjects were divided into three groups according to clinical condition and disease severity. Group 1 was formed by forty mild stage subjects with MS, group 2 was composed by twenty-six moderate stage subjects with MS and group 3 was formed by sixty-seven healthy control peers. Participants’ velocity (meters/second) and cadence (steps/minute) were assessed during a walking test, using a two-dimensional gait system. The tests were applied with motor and cognitive distractors. Statistical procedures involved repeated measures analyses of variance to test main effects for group and task. Significance was set at 5%. Results: The results showed velocity as being task- and group- dependent, id est, the impact on the outcome differs according to clinical condition (p=0.001; power of 99.9%) and to task complexity (p=0.001; power of 99.9%). Cadence, differently, showed to be task- but not group-dependent. That is, complex tasks affect cadence in both groups (p=0.001; power of 99.9%) but on a similar basis (p=0.290; power of 26.8%). Conclusion: The results suggest that in MS clinical condition and disease severity impact gait velocity on a bigger extend than cadence. Further studies should be carried out to investigate the adaptation mechanisms that occur in MS during challenging mobility situations.